Developing of Higher Order Thinking Skill in Relation and Function to Support Student’s Creative Thinking - Utari, Rahma Siska; Gustiningsi, Tria (Mathematics Education Journal, 2021)
This study aimed to produce the Higher Order Thinking Skill (HOTS)’ questions of relation and function material that had validity and practicality and also had potential effect to support student’s creative thinking. This research was a descriptive research with design research method and development study type. The questions of relation and function material developed based on characteristics of Higher Order Thinking Skill (HOTS) questions and followed stages of development study, such as: self evaluation, experts review, one-to-one, small group and field test. The subjects of this research were 38 students of eight grader from SMP Negeri 17 Palembang. They participated on one-to-one, small group and field test. Data collected using walkthroughs, interviews, questionnaires and tests. Validity of questions knew form experts review result based on content, construct and language. Practicality of questions knew from small group result about student’ understanding of purpose of questions and procedural of answering questions. Potential effect did known by test on field test stage. The result showed the HOTS’ questions of relation and function material truly supported student’s creative thinking. DOI: https://doi.org/10.22342/jpm.15.1.12876.49-60